2022
DOI: 10.1111/aas.14049
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance crew‐initiated non‐conveyance in the Helsinki EMS system—A retrospective cohort study

Abstract: Background: Ambulance patients are usually transported to the hospital in the emergency medical service (EMS) system. The aim of this study was to describe the nonconveyance practice in the Helsinki EMS system and to report mortality following non-conveyance decisions. Methods:All prehospital patients ≥16 years attended by the EMS but not transported to a hospital during 2013-2017 were included in the study. EMS mission-and patientrelated factors were collected and examined in relation to patient death within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The present study showed that >70% of suspected epileptic seizure patients requiring transportation to a hospital were similarly identified by dispatchers and paramedics, a finding that is comparable to or even better than identifying acute stroke [36]. On the other hand, in this study, the nonconveyance rate of 25% was in the lower half of the previously reported 16.3%-45% [10,[13][14][15] and was significantly lower than that of the general EMS population [22]. It has been speculated that a higher proportion would be suitable for home management if paramedics felt appropriately supported [13,37].…”
Section: Economic Burdensupporting
confidence: 61%
See 1 more Smart Citation
“…The present study showed that >70% of suspected epileptic seizure patients requiring transportation to a hospital were similarly identified by dispatchers and paramedics, a finding that is comparable to or even better than identifying acute stroke [36]. On the other hand, in this study, the nonconveyance rate of 25% was in the lower half of the previously reported 16.3%-45% [10,[13][14][15] and was significantly lower than that of the general EMS population [22]. It has been speculated that a higher proportion would be suitable for home management if paramedics felt appropriately supported [13,37].…”
Section: Economic Burdensupporting
confidence: 61%
“…Patients who are not independent in the activities of daily living or do not meet the abovementioned criteria for seizures are transported to the four other hospital EDs. Ambulance crews can also leave a well-recovering patient on the scene according to the nonconveyance protocol [22].…”
Section: Hospital System and Ems Transport Destinationmentioning
confidence: 99%
“…Consequently, the quality of patient care relies heavily on factors such as the clinicians’ competence, experience, organizational support, and adherence to guidelines [ 3 , 4 ]. The ambulance assignments have increased over time [ 5 – 7 ] and the non-conveyed patients constitute a significant and expanding proportion (3.7–93.7%) of the total patients attended to and cared for by ambulance services [ 3 , 8 10 ]. In care encounters ending with a non-conveyance decision, ambulance clinicians have recognized the complexity of the processes for non-conveyance decisions, involving a balancing act of various expectations and encountering challenges due to limited organizational support [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-acuity conditions include (but are not limited to) soft tissue injuries; minor falls; musculoskeletal back pain; gastroenteritis symptoms; headaches, e.g., migraine; and dizziness or vertigo from benign causes [ 5 ]. In fact, the utilisation by the public of ambulance services for these low-acuity conditions, has been increasing both within Australia and internationally [ 1 , 3 , 4 , 5 , 6 , 7 ]. For example, it was reported by one state ambulance service in Australia that 53% of patients assessed by emergency paramedics were either non-acute (i.e., low acuity) or did not require transport to an ED [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the growing proportion of low acuity conditions attended to by ambulance services, there is a varying percentage of patients that are deemed to not require transport to hospital [ 3 , 6 , 10 , 11 , 12 , 13 , 14 ]. Whilst many of these patients can safely remain in the community, there is a cohort who still require some form of health or medical care [ 15 ].…”
Section: Introductionmentioning
confidence: 99%